Characterisation of Thomas in the Fourth Gospel - Thomaskutty, Johnson (HTS teologiese studies, 2020)
Thomas appears four times within the narrative framework of the Fourth Gospel (Jn 11:16; 14:5; 20:24–28; 21:2). His presence in the Gospel introduces some of the strategic transitions within the macro-narrative structure. The following are some of the crucial moments that are introduced through the entry of Thomas: firstly, Thomas’ character is brought to the foreground towards the end of Jesus’ public ministry, where a transition is underway through Lazarus’ death and raising to Jesus’ death and resurrection (11:16); secondly, he appears as a significant interlocutor engaged in dialogue so that Jesus’ identity as ‘the way, the truth, and the life’ may be revealed to the disciples during his private ministry (Jn 14:5–6); thirdly, Thomas’ character appears towards the climax of the Book of Glory as he is instrumental in revealing the identity of Jesus as ‘Lord’ and ‘God’ (Jn 20:24–29); and fourthly, he appears as one of the seven disciples during the post-resurrection context in Galilee (Jn 21:2). The unique placement of Thomas communicates something significant about the character and his development within the narrative.